TINJAUAN HUKUM ISLAM TERHADAP PENGGUNAAN NAMA PRODUK KULINER NON SYARI’AH DI KABUPATEN PIDIE : Analisis Fatwa MUI Nomor 4 Tahun 2003 - Muhammad, Muhammad (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2023)
This study aims to determine the mechanism of using culinary product names, the factors that influence the use of culinary product names, as well as an overview of Islamic law on the use of non-shari'ah culinary product names in Pidie Regency. The research method used is a qualitative method, in obtaining data using the library research method (library research), as well as the field research method (field research), namely by using interview techniques, observation, and documentation. The results of this study show the mechanism for using culinary product names with strange and unique designations due to the seller's background because of the high competition in the culinary business today. The selling factor by using a strange name is very influential on sales and adds to the attractiveness of buyers. The review of Islamic law on the use of non-shari'ah culinary product names in Pidie Regency is based on the analysis of the MUI Fatwa Number 4 of 2003, the results of the analysis of the naming of culinary products in Pidie Regency are not included in the names of non-shari'ah culinary products, they are still in accordance with review of Islamic law and permissible or not contrary to the MUI Fatwa. For now, many sellers of culinary products use names that are unusual but still/appropriate and not in conflict with the MUI Fatwa. One of the names of permitted culinary products is Bakso Mercon, Meatball Rudal, Duwer Dumplings, because these names do not lead to kufr / evil as explained by MUI Fatwa No. 4 of 2003.